Positive electrode active material and preparation method thereof, positive electrode plate, secondary battery and electric device
By adjusting the average particle size and specific surface area of lithium iron phosphate particles and combining the specific surface area control of the nickel-cobalt lithium manganate particles, the processing problems existing in the mixing and preparation process of the positive electrode slurry are solved, and excellent processing performance and high capacity and kinetic performance of the secondary battery are achieved.
Patent Information
- Application Number
- CN202410026192.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-01-08
AI Technical Summary
In the prior art, when mixing the lithium nickel-cobalt manganate material and lithium iron phosphate salt material to prepare the positive electrode slurry, processing problems such as gel formation, agglomeration phenomenon, strong water absorption and difficulty in drying, etc., which affects the performance of the secondary battery.
By adjusting the average particle size and specific surface area of lithium iron phosphate particles, combined with the specific surface area control of the nickel-cobalt lithium manganate particles, a positive electrode active material with excellent processing performance was prepared. Specific measures include increasing the average particle size of lithium iron phosphate particles to 500-3000 nm and reducing their specific surface area to 3-8m2/g, and controlling the specific surface area of nickel-cobalt lithium manganate particles to 0.4-2.0m2/g.
This method effectively reduces the water absorption performance of the positive electrode slurry, reduces gel and agglomeration, improves the drying speed and degree, and takes into account the gram capacity and kinetic performance of the secondary battery.
Smart Images

Figure CN119852392A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] Nickel cobalt manganese oxide and lithium iron phosphate are commonly used lithium ion positive electrode active materials. In order to reduce the cost of lithium ion batteries, nickel cobalt manganese oxide and lithium iron phosphate can be used in combination, but there are a series of processing problems in the process of mixing nickel cobalt manganese oxide and lithium iron phosphate to prepare positive electrode slurry. Summary of the invention
[0004] This application is made in view of the above-mentioned subject, and aims to solve at least one of the technical problems existing in the prior art. To this end, this application provides a positive electrode active material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. The positive electrode active material of this application has good processing performance, while also taking into account the gram capacity of the secondary battery.
[0005] The first aspect of the present application provides a positive electrode active material, the positive electrode active material comprises lithium iron phosphate salt particles and nickel cobalt manganese oxide lithium particles, the primary average particle size of the lithium iron phosphate salt particles is 500-3000nm, the specific surface area of the lithium iron phosphate salt particles is BET 3m 2 / g-8m 2 / g, the specific surface area of the lithium nickel cobalt manganese oxide particles is 0.4m 2 / g-2.0m 2 / g.
[0006] In order to improve the electrochemical properties of lithium iron phosphate particles, they are usually nanosized to improve their ability to transmit electrons. However, the specific surface area of nanosized lithium iron phosphate particles is too large, which leads to severe water absorption. In actual application, in order to reduce costs, they are often mixed with nickel cobalt manganese oxide particles. However, in the process of preparing the mixed slurry, the lithium iron phosphate particles are prone to form gels due to their high water absorption, which brings about a series of processing problems such as low solid content and poor filtration performance. Furthermore, the high molecular weight binders used in the nickel cobalt manganese oxide positive electrode slurry, such as polyvinylidene fluoride, have a poor compatibility with nano-scale lithium iron phosphate. In this type of binder system, lithium iron phosphate particles are prone to agglomeration, which brings about processing problems. The primary average particle size of the lithium iron phosphate particles of the present application is 500-3000nm, and the specific surface area is 3m2 / g-8m 2 / g, the specific surface area of lithium nickel cobalt manganese oxide particles is 0.4m 2 / g-2.0m 2 / g. The reduced specific surface area is conducive to reducing the water absorption performance of the positive electrode slurry, thereby reducing the gelation and agglomeration phenomena during the slurry processing, and can also improve the drying speed and degree of the pole piece. At the same time, a larger primary average particle size is conducive to better dispersion of the lithium iron phosphate salt particles in the high molecular weight binder system, further reducing the occurrence of agglomeration. However, excessively large particle size and too low specific surface area will affect the kinetic performance and reduce the gram capacity. The positive electrode active material of the present application increases the primary average particle size of the lithium iron phosphate salt particles and reduces the specific surface area, and controls the two within a reasonable range, while obtaining better processing performance and taking into account the gram capacity of the secondary battery.
[0007] In any embodiment, the lithium iron phosphate particles have a molecular formula Li m1 Fe x1 P y1 O z1 Q q1 , wherein Q comprises at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤z1≤4, 0<q1≤0.1, and / or
[0008] The lithium nickel cobalt manganese oxide particles have a molecular formula of LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2 O2, wherein R includes at least one of Cr, Ti, V, Mg, Al, and Nb, 0≤x2<1, 0<y2<1, 0<z2<1, 0<x2+y2+z2<1.
[0009] Doping the above elements in lithium iron phosphate particles and / or lithium nickel cobalt manganese oxide particles helps to improve the ion transport capacity of the positive electrode active material. The above elements can explain vacancies in the particle lattice or change the interatomic bond length, facilitating the movement of lithium ions in the lattice, thereby effectively improving the conductivity of the particles themselves and improving the kinetic properties of the positive electrode active material.
[0010] In any embodiment, the primary average particle size of the lithium iron phosphate salt particles is 650-2500 nm.
[0011] Controlling the primary average particle size of lithium iron phosphate salt particles within a reasonable range will help to further improve the processing performance of the positive electrode slurry while taking into account the gram capacity of the secondary battery.
[0012] In any embodiment, the BET of the lithium iron phosphate particles is 4m 2 / g-7m 2 / g, the BET of the nickel cobalt manganese oxide particles is 0.6m 2 / g-2.0m 2 / g.
[0013] If the BET of lithium iron phosphate particles and / or lithium nickel cobalt manganese oxide particles is too high, the particles will absorb more water and affect the processing performance of the mixed positive electrode slurry. However, if the BET of lithium iron phosphate particles and lithium nickel cobalt manganese oxide particles is too low, their gram capacity and kinetic performance will be reduced. Control the BET of lithium iron phosphate particles to 4m 2 / g-7m 2 / g, and the BET of the nickel cobalt manganese oxide particles is controlled at 0.6m 2 / g-2.0m 2 / g, which is beneficial to further balance the processing performance of the positive electrode slurry and the gram capacity of the secondary battery.
[0014] In any embodiment, calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is Cx weight %, and the ratio z of the BET of the lithium iron phosphate salt particles to the Cx satisfies 1.5≤z≤8.5, and optionally, the z satisfies 3≤z≤6.
[0015] In the present application, the ratio z of the specific surface area BET to Cx of the lithium iron phosphate particles can characterize the uniform density of the carbon contained in the lithium iron phosphate particles. When the primary average particle size and carbon content of the lithium iron phosphate particles remain unchanged, the lower the ratio z, the more uniform and dense the carbon contained in the lithium iron phosphate particles. Improving the uniform density of the contained carbon is conducive to further improving the kinetic performance and gram capacity of the lithium iron phosphate particles, but too high a carbon coating density will affect the insertion and extraction of lithium ions, and to a certain extent affect the kinetic performance and gram capacity of the secondary battery. The range of the ratio z of the embodiment of the present application is conducive to the carbon contained in the lithium iron phosphate particles having a suitable uniform density, which is conducive to improving the conductivity of the particle surface, and is conducive to further improving the kinetic performance and gram capacity of the secondary battery.
[0016] In any embodiment, based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is 0.8 wt%-2.0 wt%. Optionally, based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is 1.0 wt%-1.6 wt%.
[0017] Increasing the carbon content of lithium iron phosphate particles helps to improve its conductivity, thereby improving the kinetic performance and gram capacity, but too high a carbon content may affect the insertion and extraction of lithium ions, and to some extent affect the gram capacity of the secondary battery. The carbon content range of the present application helps to further obtain better kinetic performance and gram capacity.
[0018] In any embodiment, the Q includes at least one of Ti, V, Mg, and Nb. Optionally, the Q is Ti;
[0019] Calculated based on the total weight of the lithium iron phosphate salt particles, the content of Q in the lithium iron phosphate salt particles is 1000-10000 ppm. Optionally, based on the total mass of the lithium iron phosphate salt particles, the content of Q in the lithium iron phosphate salt particles is 2500-6000 ppm.
[0020] The content of doping elements in existing lithium iron phosphate particles is generally low or no doping elements are added. Increasing the content of Q element in lithium iron phosphate particles can help further improve the bulk ion transport capacity of lithium iron phosphate particles and improve their kinetic performance. However, as the content of Q element further increases, the bulk ion transport capacity may not continue to increase, and it may also occupy the position of lithium ions, affecting the performance of gram capacity. The range of Q element in this application helps to further obtain better kinetic performance and gram capacity.
[0021] In any embodiment, the ratio of Dv50 of the lithium iron phosphate salt particles to the Dv50 of the nickel cobalt manganese oxide particles is 1:(1-25). Optionally, the ratio of D50 value of the lithium iron phosphate salt particles to the Dv50 of the nickel cobalt manganese oxide particles is 1:(1-20).
[0022] In any embodiment, the Dv50 of the lithium iron phosphate salt particles is 500-5000 nm. Optionally, the Dv50 of the lithium iron phosphate salt particles is 700-2500 nm.
[0023] In any embodiment, the Dv50 of the nickel cobalt lithium manganese oxide particles is 1200-20000 nm. Optionally, the Dv50 of the nickel cobalt lithium manganese oxide particles is 3000-15000 nm.
[0024] Controlling the Dv50 ratio range and value range of the lithium iron phosphate salt particles and the nickel cobalt manganese oxide particles in the embodiment of the present application within the above-mentioned range is conducive to the lithium iron phosphate salt particles being evenly and tightly filled between the nickel cobalt manganese oxide particles, alleviating the agglomeration phenomenon of the single-component particles in the composite positive electrode active material, and improving the compaction density of the positive electrode active material.
[0025] In any embodiment, the Dv50 of the lithium iron phosphate salt particles is 870-1500 nm, and the Dv50 of the lithium nickel cobalt manganese oxide particles is 1800-4200 nm.
[0026] In any embodiment, based on the total mass of the positive electrode active material, the mass percentage of the lithium iron phosphate salt particles is 5%-80%, and can be optionally 15%-50%.
[0027] In any embodiment, based on the total mass of the positive electrode active material, the mass percentage of the lithium nickel cobalt manganese oxide particles is 20%-95%, and optionally 50%-85%.
[0028] Controlling the mass percentage of lithium iron phosphate particles and lithium nickel cobalt manganese oxide particles within the above range helps to further balance the electrical properties and cost of the positive electrode active material.
[0029] In any embodiment, the capacity ratio of the lithium iron phosphate salt particles is η≥88%, where η is defined as:
[0030] The battery having the lithium iron phosphate particles as the positive electrode active material is charged and discharged twice at a constant current of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted at a discharge voltage of 2.0V is recorded as C2, and η=C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50uA.
[0031] The capacity ratio η of the lithium iron phosphate salt particles can reflect its kinetic performance and platform retention performance, which can be adjusted by adjusting the primary average particle size, carbon content, carbon source and carbon film-forming agent ratio, modifier and its content of the lithium iron phosphate salt particles. The η value of the lithium iron phosphate salt particles in the embodiment of the present application is ≥88%, which has good kinetic performance. At the same time, when the η value is high, the secondary battery can still maintain good power performance when discharged to a low SOC, that is, the battery with a high η value has a small voltage drop value when the battery is discharged at a low power and a large current. When the positive active material of the present application is discharged, the nickel cobalt manganese oxide particles have a high voltage and participate in the discharge first. The lithium iron phosphate particles participate in the discharge later and will withstand a large current and easily produce polarization. The lithium iron phosphate particles of the present application have high kinetic performance, which is beneficial to improving the discharge power performance of the secondary battery.
[0032] In any embodiment, the lithium iron phosphate salt particles satisfy at least one of (a)-(e):
[0033] a) the Dv10 of the lithium iron phosphate particles is ≥200nm;
[0034] b) the Dv90 of the lithium iron phosphate particles is ≤10000m;
[0035] c) the Dv99 of the lithium iron phosphate particles is ≤12000nm;
[0036] d) The powder compaction density of the lithium iron phosphate salt under a pressure of 3T is ≥2.25g / cm 3 ;
[0037] e) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
[0038] By making the lithium iron phosphate salt particles satisfy at least one of (a)-(e), the lithium iron phosphate salt particles can better achieve the technical effect of the present application.
[0039] The second aspect of the present application provides a method for preparing a positive electrode active material, the method comprising: mixing the lithium iron phosphate salt particles and the lithium nickel cobalt manganese oxide particles,
[0040] The preparation process of the lithium iron phosphate salt particles includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, optionally a carbon source, optionally a carbon film-forming agent, and optionally a modifier, and performing at least two sintering steps, wherein:
[0041] The temperature of the first sintering is 500℃-760℃, and can be 550℃-720℃;
[0042] The temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C.
[0043] Compared with the traditional preparation method that uses high temperature to achieve particle growth, the lithium iron phosphate salt particles of the present application are sintered twice, and controlling the temperature of the two sinterings is conducive to preparing lithium iron phosphate salt particles with the primary average particle size and specific surface area of the present application. Furthermore, in the conventional high-temperature sintering process, the carbon coating layer on the surface of the particles is prone to cracking, reducing the integrity of the carbon coating. The present application synthesizes large particles at low temperature, which is conducive to reducing floating carbon and improving the consistency and uniformity of the surface carbon coating.
[0044] In any embodiment, the lithium iron phosphate particles are mainly obtained by the following preparation method: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and sintering at least twice, wherein:
[0045] The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%;
[0046] The carbon content of the material after the second sintering is 0.8 wt % to 2.0 wt %, and can be optionally 1.0 wt % to 1.6 wt %.
[0047] Adding a carbon source before the first sintering can effectively reduce the trivalent iron in the raw material and improve the purity and stability of the product. Furthermore, adding a lower carbon source content during the first sintering process is beneficial to reducing the barrier effect of the carbon layer on the growth of lithium iron phosphate particles, which is beneficial to the crystallization growth of the lithium iron phosphate salt particle precursor at a lower temperature. At the same time, the low carbon content during the first sintering process is also beneficial to the solid-phase diffusion reaction between the modifier that may be added and the lithium iron phosphate salt material, which is beneficial to achieve a higher concentration of metal ion doping. Increasing the added carbon content in the second sintering further improves the uniformity and integrity of the coating, which is beneficial to obtaining lithium iron phosphate salt particles with the carbon content of the embodiment of the present application.
[0048] In any embodiment, the lithium iron phosphate salt particles contain at least one of Ti, V, Mg, and / or Nb elements, and the content of the element is 1000ppm-10000ppm, optionally 2500ppm-6000ppm, calculated based on the total weight of the lithium iron phosphate salt particles.
[0049] In any embodiment, the first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein:
[0050] The Dv50 of the product after the first pulverization is 300nm-1200nm, and can be optionally 400nm-1100nm;
[0051] The Dv50 of the product after the second pulverization is 500nm-5000nm, and can be optionally 700nm-2500nm.
[0052] Controlling the Dv50 of the product after the first pulverization within the above range is conducive to reducing the growth barrier effect of the added carbon source and the possible doping elements on the lithium iron phosphate salt particle precursor crystal, and is helpful to prepare a micron-sized lithium iron phosphate salt particle precursor. By controlling the Dv50 value of the product after the second pulverization within the above range, it is helpful to obtain lithium iron phosphate salt particles having the primary average particle size of the present application.
[0053] A third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material as described in the present application or the positive electrode active material obtained by the preparation method as described in the present application.
[0054] In any embodiment, the compaction density of the positive electrode sheet is 3.0 g / cm 3 -3.5g / cm 3 .
[0055] A fourth aspect of the present application provides a secondary battery, which includes the positive electrode plate as described in the present application.
[0056] A fifth aspect of the present application provides an electrical device, which includes the secondary battery described in the present application.
[0057] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a slice diagram of the positive electrode sheet of Example 1 of the present application. Figure 1 a is a cross-section of the positive electrode under 5k times magnification and Figure 1 b is a slice image of the positive electrode under 10k times magnification.
[0059] Figure 2 This is a scanning electron microscope image of the lithium iron phosphate particles of Example 1 of the present application.
[0060] Figure 3 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0061] Figure 4 yes Figure 3 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0062] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.
[0063] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0064] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0065] Figure 8 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0066] Fig. 9 This is a scanning electron microscope image of lithium iron phosphate particles with primary particle size marked according to one embodiment of the present application.
[0067] Description of reference numerals:
[0068] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0069] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0070] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0071] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0072] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0073] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0074] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0075] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0076] In order to balance the battery cost and the electrical performance of the battery, lithium iron phosphate materials can be mixed with nickel cobalt manganese oxide materials to prepare positive electrode active materials. Lithium iron phosphate particles have the problem of poor electrical performance. In order to improve the electrical properties of lithium iron phosphate particles, they are usually nano-sized to improve their ability to transmit electrons. However, in the process of mixing lithium iron phosphate particles with nickel cobalt manganese oxide particles to prepare slurry, the positive electrode slurry is easy to form gel, and the agglomeration phenomenon is serious, which brings a series of processing problems such as low solid content, poor filtration performance, strong water absorption of the pole piece, and difficulty in drying. The present application increases the primary average particle size of the lithium iron phosphate particles and reduces its specific surface area and controls it within a reasonable range, while taking into account the gram capacity of the secondary battery while obtaining better processing performance. At the same time, the reduction of BET and water absorption performance of lithium iron phosphate particles is also conducive to reducing the occurrence of side reactions and improving the life of the battery cell.
[0077] [Positive electrode active material]
[0078] Based on this, the present application provides a positive electrode active material, the positive electrode active material includes lithium iron phosphate salt particles and lithium nickel cobalt manganese oxide particles, the primary average particle size of the lithium iron phosphate salt particles is 500-3000nm, and the specific surface area of the lithium iron phosphate salt particles is 3m 2 / g-8m 2 / g, and the specific surface area of lithium nickel cobalt manganese oxide particles is 0.4m 2 / g-2.0m 2 / g.
[0079] In this application, the term "primary average particle size" refers to the average of the primary particle sizes of all particles, wherein the primary particle size refers to the longest distance between two points on the edge in the cross-sectional view. Fig. 9 As shown in the scanning electron microscope image of lithium iron phosphate particles, the line segment marked by double arrows in the particles is the primary particle size defined in this application.
[0080] In the present application, the term "specific surface area" or "BET" refers to the total area per unit mass of particles. In the present application, the BET of lithium iron phosphate particles is related to factors such as the primary average particle size of the lithium iron phosphate particles, the carbon content, the density of the carbon coating, the degree of fit between the carbon and the particles, and the looseness and porosity of the particles.
[0081] In some embodiments, the lithium iron phosphate salt particles are primary particles.
[0082] In this article, "primary particles" refer to particles that do not have obvious agglomeration interfaces in the particle scanning electron microscope image, but may have tiny pores and point or line defects, which are different from powder particles that are the smallest units without structures such as stacking and flocculation.
[0083] In some embodiments, the lithium iron phosphate salt particles are single crystal particles and / or polycrystalline particles.
[0084] In this article, the term "single crystal" refers to a crystal with a complete structure grown from a single crystal nucleus. The single crystal of the present application is a whole under the field of view of a transmission electron microscope photograph, and there is no grain boundary in the single crystal.
[0085] In some embodiments, the single crystal of the present application may have tiny defects, for example, micro-pores inside, a small number of points and surfaces, or a small number of particles adhering to each other on the surface of a particle.
[0086] As used herein, the term "polycrystalline" refers to a crystal composed of small single crystal particles randomly oriented together, with grain boundaries existing within the polycrystalline.
[0087] In some embodiments, based on the total number of lithium iron phosphate particles, the number of single crystal particles accounts for greater than or equal to 90%. The number of single crystal particles is controlled within the above range. Compared with polycrystalline and secondary agglomerates, the proportion of single crystal particles is higher, which is conducive to reducing BET and improving processing performance.
[0088] The primary average particle size of the lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be tested by scanning electron microscopy and long diameter statistical method. As an example, an argon ion beam is used to cut the pole piece perpendicular to the large surface of the positive electrode pole piece to expose the cross section, and the cross section is photographed by a scanning electron microscope. The particle size of the lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Specifically, the total number of lithium iron phosphate salt particles with a primary particle size greater than 80nm and the primary particle size and the sum of the lithium iron phosphate salt particles with a primary particle size greater than 80nm can be counted in the electron microscope scanning photo. The primary average particle size of the lithium iron phosphate salt particles = the primary particle size and the sum of the lithium iron phosphate salt particles / the total number of lithium iron phosphate salt particles. Among them, in the primary particle size statistical process, particles with a primary particle size of 0 < ≤ 80nm are not within the statistical range.
[0089] In order to improve the electrical properties of lithium iron phosphate particles, they are usually nanosized to improve their ability to transmit electrons. However, the specific surface area of nanosized lithium iron phosphate particles is too large, which leads to severe water absorption. Therefore, in the process of mixing with nickel cobalt manganese oxide particles to prepare slurry, lithium iron phosphate particles are prone to form gels due to high water absorption, resulting in a series of processing problems such as low solid content and poor filtration performance. Furthermore, nanoscale lithium iron phosphate particles and high molecular weight binders commonly used in the preparation of nickel cobalt manganese oxide particles positive active materials, such as polyvinylidene fluoride, have a problem of poor compatibility. In this type of binder system, lithium iron phosphate particles are prone to agglomeration, which brings about processing problems. The primary average particle size of the lithium iron phosphate particles of the present application is 500-3000nm, and the specific surface area of the lithium iron phosphate particles is further adjusted to 3m 2 / g-8m 2 / g, the specific surface area of lithium nickel cobalt manganese oxide particles is 0.4m 2 / g-2.0m 2 / g. The reduced specific surface area is conducive to reducing the water absorption performance of the positive electrode slurry, thereby reducing the gelation and agglomeration phenomena during the slurry processing, and can also improve the drying speed and degree of the slurry. At the same time, a larger primary average particle size is conducive to better dispersion of lithium iron phosphate salt particles in a high molecular weight binder system, further reducing the occurrence of agglomeration. However, excessively large particle size and too low specific surface area will reduce the gram capacity of the positive electrode active material. The positive electrode active material of the present application increases the primary average particle size of the lithium iron phosphate salt particles and reduces its specific surface area, and reduces the specific surface area of the nickel cobalt manganese oxide lithium particles, and controls the two within a reasonable range, while obtaining better processing performance and taking into account the gram capacity of the secondary battery.
[0090] In some embodiments, the lithium iron phosphate salt particles have the molecular formula Li m1 Fe x1 P y1 O z1 Qq1 , wherein Q comprises at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤z1≤4, 0<q1≤0.1, and / or
[0091] Lithium nickel cobalt manganese oxide particles have the molecular formula LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2 O2, wherein R includes at least one of Cr, Ti, V, Mg, Al, and Nb, 0≤x2<1, 0<y2<1, 0<z2<1, 0<x2+y2+z2<1.
[0092] In some embodiments, the lithium iron phosphate salt particles have the molecular formula Li m1 Fe x1 P y1 O z1 Q q1 , m1 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x1 can be 0.9, 1.0, y1 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, z1 can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, and q1 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.
[0093] In some embodiments, the lithium nickel cobalt manganese oxide particles have the molecular formula LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2 O2, R includes at least one of Ti, V, Mg, and Nb.
[0094] In some embodiments, the lithium nickel cobalt manganese oxide particles have the molecular formula LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2O2, x2 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.5, 0.7, 0.8, 0.9, y2 can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.5, 0.7, 0.8, 0.9, z2 can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.5, 0.7, 0.8, 0.9. In some embodiments, the ratio of lithium and oxygen content in the lithium nickel cobalt manganese oxide particles will fluctuate during battery formation and cycling.
[0095] Doping the above elements in lithium iron phosphate particles and / or lithium nickel cobalt manganese oxide particles helps to improve the ion transport capacity of the positive electrode active material. The above elements can explain vacancies in the particle lattice or change the interatomic bond length, facilitating the movement of lithium ions in the lattice, thereby effectively improving the conductivity of the particles themselves and improving the kinetic properties of the positive electrode active material.
[0096] In some embodiments, the primary average particle size of the lithium iron phosphate salt particles is 650-2500 nm.
[0097] In some embodiments, the primary average particle size of the lithium iron phosphate particles can be 500nm, 550nm, 600nm, 650nm, 700nm, 730nm, 750nm, 780nm, 800nm, 830nm, 850nm, 870nm, 900nm, 950nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 2000nm, 2100nm, 2200nm, 2300nm, 2400nm, 2500nm, 2600nm, 2700nm, 2800nm, 2900nm, 3000nm, or a value in the range composed of any two of the above primary average particle sizes.
[0098] Controlling the primary average particle size of lithium iron phosphate salt particles within a reasonable range will help to further improve the processing performance of the positive electrode slurry while taking into account the gram capacity of the secondary battery.
[0099] In some embodiments, the BET of the lithium iron phosphate particles is 4 m 2 / g-7m 2 / g, the BET of lithium nickel cobalt manganese oxide particles is 0.6m 2 / g-2.0m 2 / g.
[0100] In some embodiments, the specific surface area of the lithium iron phosphate particles can be 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, or a value within the range of the BET composition of the specific surface areas of any two of the above-mentioned lithium iron phosphate particles.
[0101] In some embodiments, the specific surface area BET of the lithium nickel cobalt manganese oxide particles can be 0.6 m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2.0m 2 / g, or a value within the range of the specific surface area BET composition of any two of the above lithium nickel cobalt manganese oxide particles.
[0102] The BET specific surface area of the particles can be measured by methods and equipment known in the art. For example, it can be tested according to the gas adsorption method with reference to GB / T 19587-2017. As an example, lithium iron phosphate particles are taken as samples and placed in a sample tube, the sample tube is immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures is measured at a relative pressure of 0.05-0.30. The sample monolayer adsorption amount is obtained based on the BET multilayer adsorption theory and its formula, thereby obtaining the specific surface area of the sample.
[0103] If the BET of lithium iron phosphate particles and / or lithium nickel cobalt manganese oxide particles is too high, the particles will absorb more water and affect the processing performance of the mixed positive electrode slurry. If the BET of lithium iron phosphate particles and lithium nickel cobalt manganese oxide particles is too low, their gram capacity will be reduced. Control the BET of lithium iron phosphate particles within 4m 2 / g-7m 2 / g, and the BET of the nickel cobalt manganese oxide particles is controlled at 0.6m 2 / g-2.0m 2 / g, which is beneficial to further balance the processing performance of the positive electrode slurry and the gram capacity of the secondary battery.
[0104] In some embodiments, the carbon content of the lithium iron phosphate salt particles is Cx weight %, calculated based on the total weight of the lithium iron phosphate salt particles, and the ratio z of BET to Cx of the lithium iron phosphate salt particles satisfies 1.5≤z≤8.5.
[0105] In some embodiments, z satisfies 3≤z≤6.
[0106] In some embodiments, z can be 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.3, 4.5, 4.8, 5, 5.3, 5.5, 5.8, 6, 6.3, 6.5, 6.8, 7, 7.3, 7.5, 7.8, 8, 8.3, 8.5, or a value in the range consisting of any two of the above z values.
[0107] In the present application, the ratio z of the specific surface area BET to Cx of the lithium iron phosphate salt particles can characterize the uniform density of the carbon contained in the lithium iron phosphate salt particles. When the primary average particle size and carbon content of the lithium iron phosphate salt particles remain unchanged, the lower the ratio z, the higher the coating utilization rate of the carbon in the particles, the less floating carbon, and the more uniform and dense the carbon contained in the lithium iron phosphate salt particles. Improving the uniform density of the contained carbon is conducive to improving the kinetic performance and gram capacity of the lithium iron phosphate salt particles. However, too high a carbon coating density may affect the insertion and extraction of lithium ions, and to a certain extent affect the kinetic performance and gram capacity of the secondary battery. The range of the ratio z of the embodiment of the present application is conducive to the carbon contained in the lithium iron phosphate salt particles having a suitable uniform density, which is conducive to improving the conductivity of the particle surface, and is conducive to further improving the kinetic performance and gram capacity of the secondary battery.
[0108] In some embodiments, the carbon content of the lithium iron phosphate salt particles is 0.8 wt % to 2.0 wt %, calculated based on the total weight of the lithium iron phosphate salt particles.
[0109] In some embodiments, the carbon content of the lithium iron phosphate salt particles is 1.0 wt % to 1.6 wt %, based on the total weight of the lithium iron phosphate salt particles.
[0110] In some embodiments, the carbon content of the lithium iron phosphate salt particles is 0.8 weight %, 0.9 weight %, 1.0 weight %, 1.1 weight %, 1.2 weight %, 1.3 weight %, 1.4 weight %, 1.5 weight %, 1.6 weight %, 1.7 weight %, 1.8 weight %, 1.9 weight %, 2.0 weight %, or a value in the range of any two of the above carbon contents, calculated based on the total weight of the lithium iron phosphate salt particles.
[0111] In some embodiments, the carbon contained in the lithium iron phosphate salt particles is coated on the surface of the particles. In some embodiments, the carbon contained in the lithium iron phosphate salt particles is embedded in the particles. In some embodiments, the carbon contained in the lithium iron phosphate salt particles is partially coated on the surface of the particles and partially embedded in the particles.
[0112] The carbon content of the ferric phosphate particles can be measured by methods and equipment known in the art. For example, the test can be performed with reference to GB / T 20123-2006 / ISO 15350:2000.
[0113] Increasing the carbon content of lithium iron phosphate particles helps to improve its conductivity, thereby improving kinetic performance and gram capacity, but too high a carbon content may affect the insertion and extraction of lithium ions, and to a certain extent affect the gram capacity of the secondary battery. The carbon content range of the embodiment of the present application helps to further obtain better kinetic performance and gram capacity.
[0114] In some embodiments, Q comprises at least one of Ti, V, Mg, and Nb. In some embodiments, Q is Ti.
[0115] In some embodiments, the content of Q in the lithium iron phosphate salt particles is 1000-10000 ppm, calculated based on the total weight of the lithium iron phosphate salt particles.
[0116] In some embodiments, based on the total mass of the lithium iron phosphate salt particles, the content of Q in the lithium iron phosphate salt particles is 2500-6000 ppm.
[0117] In some embodiments, the content of Q in the lithium iron phosphate salt particles is 1000ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, or a value in the range consisting of any two of the above contents of Q.
[0118] The content of Q in the lithium iron phosphate salt particles, for example, the content of Ti, can be measured by methods and equipment known in the art. For example, the test can be performed with reference to GB / T 33822-2017.
[0119] The content of doping elements in existing lithium iron phosphate particles is generally low or no doping elements are added. Increasing the content of Q element in lithium iron phosphate particles can help further improve the bulk ion transport capacity of lithium iron phosphate particles and improve their kinetic performance. However, as the content of Q element further increases, the bulk ion transport capacity may not continue to increase, and it may also occupy the position of lithium ions, affecting the performance of gram capacity. The range of Q element in this application helps to further obtain better kinetic performance and gram capacity.
[0120] In some embodiments, the ratio of Dv50 of the lithium iron phosphate salt particles to Dv50 of the lithium nickel cobalt manganese oxide particles is 1:(1-25).
[0121] In some embodiments, the ratio of the D50 value of the lithium iron phosphate salt particles to the Dv50 value of the lithium nickel cobalt manganese oxide particles is 1:(1-20).
[0122] In some embodiments, the ratio of Dv50 of lithium iron phosphate salt particles to Dv50 of lithium nickel cobalt manganese oxide particles can be 1:1, 1:3, 1:5, 1:7, 1:10, 1:13, 1:15, 1:20, 1:23 or 1:25, or a value in the range of the ratios of Dv50 of any two of the above lithium iron phosphate salt particles to Dv50 of lithium nickel cobalt manganese oxide particles.
[0123] In some embodiments, the Dv50 of the lithium iron phosphate salt particles is 500-5000 nm.
[0124] In some embodiments, the Dv50 of the lithium iron phosphate salt particles is 700-2500 nm.
[0125] In some embodiments, the Dv50 of the lithium iron phosphate salt particles is 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 3000nm, 3300nm, 3500nm, 3700nm, 4000nm, 4300nm, 4500nm, 4700nm, 5000nm, or a value in the range composed of the Dv50 of any two of the above lithium iron phosphate salt particles.
[0126] In some embodiments, the Dv50 of the lithium nickel cobalt manganese oxide particles is 1200-20000 nm.
[0127] In some embodiments, the Dv50 of the lithium nickel cobalt manganese oxide particles is 3000-15000 nm.
[0128] In some embodiments, the Dv50 of the lithium nickel cobalt manganese oxide particles can be 1200nm, 1500nm, 1700nm, 2000nm, 2300nm, 2500nm, 2700nm, 3000nm, 3300nm, 3500nm, 4000nm, 4300nm, 4500nm, 4700nm, 5000nm, 6000nm, 7000nm, 8000nm, 9000nm, 10000nm, 11000nm, 12000nm, 13000nm, 14000nm, 15000nm, 16000nm, 17000nm, 18000nm, 19000nm, 20000nm, or a value in a range consisting of the Dv50 of any two of the foregoing lithium nickel cobalt manganese oxide particles.
[0129] In the present application, the term "Dv50" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 50%.
[0130] The Dv50 of the lithium iron phosphate salt particles and the Dv50 of the lithium nickel cobalt manganese oxide particles can be measured by methods and equipment known in the art. For example, it can be measured with reference to GB / T19077.1-2016 using a laser particle size analyzer (Malvern MasterSize 3000).
[0131] Controlling the Dv50 ratio range and value range of the lithium iron phosphate salt particles and the nickel cobalt manganese oxide particles in the embodiment of the present application within the above-mentioned range is conducive to the lithium iron phosphate salt particles being evenly and tightly filled between the nickel cobalt manganese oxide particles, alleviating the agglomeration phenomenon of the single-component particles in the composite positive electrode active material, and improving the compaction density of the positive electrode active material.
[0132] In some embodiments, the Dv50 of the lithium iron phosphate salt particles is 870-1500 nm, and the Dv50 of the lithium nickel cobalt manganese oxide particles is 1800-4200 nm.
[0133] In some embodiments, the mass percentage of the lithium iron phosphate salt particles is 5%-80% based on the total mass of the positive electrode active material.
[0134] In some embodiments, the mass percentage of the lithium iron phosphate salt particles is 15%-50% based on the total mass of the positive electrode active material.
[0135] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the lithium iron phosphate salt particles can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or a value in the range of the mass percentages of any two of the above-mentioned lithium iron phosphate salt particles.
[0136] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the lithium nickel cobalt manganese oxide particles is 20%-95%.
[0137] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the lithium nickel cobalt manganese oxide particles is 50%-85%.
[0138] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the lithium nickel cobalt manganese oxide particles can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or a value in the range of the mass percentages of any two of the above lithium nickel cobalt manganese oxide particles.
[0139] Controlling the mass percentage of lithium iron phosphate particles and lithium nickel cobalt manganese oxide particles within the above range helps to further balance the electrical properties and cost of the positive electrode active material.
[0140] In some embodiments, the capacity of the lithium iron phosphate particles is η≥88%, where η is defined as:
[0141] The battery with lithium iron phosphate particles as the positive electrode active material was charged and discharged twice at a constant current of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted at a discharge voltage of 3.2V was recorded as C1, and the capacity value extracted at a discharge voltage of 2.0V was recorded as C2, and η = C1 / C2. Among them, the charging process includes constant voltage charging, constant voltage 3.75V, and constant voltage cut-off current 50uA.
[0142] In some embodiments, η can be 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, or a value in the range consisting of any two of the above values of η.
[0143] The η value of lithium iron phosphate salt particles can be measured by methods and equipment known in the art. As an example, firstly, a button cell is prepared with lithium iron phosphate salt particles as the positive electrode active material. The specific button cell preparation process is as follows: 2.0000g of lithium iron phosphate salt particles are mixed with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then added to 2.5g of organic solvent N-methylpyrrolidone, and mixed thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum heat preservation at 120°C for 12h to obtain a positive electrode sheet. Weigh the weight of the positive electrode sheet, wherein the loading amount of lithium iron phosphate salt particles is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.
[0144] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V was extracted and recorded as C1, and the capacity value at a discharge voltage of 2.0V was extracted and recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50uA.
[0145] The capacity ratio η of the lithium iron phosphate salt particles can reflect its kinetic performance and platform retention performance, which can be adjusted by adjusting the primary average particle size, carbon content, carbon source and carbon film-forming agent ratio, modifier and its content of the lithium iron phosphate salt particles. The η value of the lithium iron phosphate salt particles in the embodiment of the present application is ≥88%, which has good kinetic performance. At the same time, when the η value is high, the secondary battery can still maintain good power performance when discharged to a low SOC, that is, the battery with a high η value has a small voltage drop value when the battery is discharged at a low power and a large current. When the positive active material of the embodiment of the present application is discharged, the nickel cobalt manganese oxide particles have a high voltage and participate in the discharge first. The lithium iron phosphate particles participate in the discharge later and will withstand a large current and easily produce polarization. The lithium iron phosphate particles of the present application have high kinetic performance, which is beneficial to improving the discharge power performance of the secondary battery.
[0146] In some embodiments, the lithium iron phosphate salt particles satisfy at least one of (a)-(e):
[0147] a) Dv10 of lithium iron phosphate particles ≥ 200nm;
[0148] b) Dv90 of lithium iron phosphate particles ≤ 10000m;
[0149] c) Dv99 of lithium iron phosphate particles ≤ 12000nm;
[0150] d) The powder compaction density of lithium iron phosphate at 3T pressure is ≥2.25g / cm 3 ;
[0151] e) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
[0152] As used herein, the term "Dv10" refers to the particle size corresponding to the particle having a volume cumulative particle size distribution percentage of 10%.
[0153] As used herein, the term "Dv90" refers to the particle size at which the volume cumulative particle size distribution percentage in the particles reaches 90%.
[0154] As used herein, the term "Dv99" refers to the particle size corresponding to the 99% cumulative particle size distribution percentage in the particles.
[0155] In this article, the term "powder compaction density" refers to the density of a compact with a certain density and strength formed when the powder moves and deforms during the external compression process, larger gaps are filled, the contact area between particles increases, the attraction between atoms is generated, and the mechanical fit between particles is enhanced. The unit is g / cm 3 .
[0156] In some embodiments, the lithium iron phosphate salt particles have a Dv10<Dv50.
[0157] In some embodiments, the lithium iron phosphate salt particles have a Dv90>Dv50.
[0158] The Dv10, Dv90 and Dv99 of the lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be measured with reference to GB / T19077.1-2016 using a laser particle size analyzer (Malvern Master Size 3000).
[0159] Under different pressures, the powder compaction density of lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, GB / T 24533-2009 can be referred to and measured using a compaction density instrument. Specifically, a certain amount of lithium iron phosphate salt particles are placed on a special compaction mold (the mold diameter is known), and the mold is hollow in the middle and has a metal disc above and below. The lithium iron phosphate salt particles are placed between the metal discs, a metal cylinder is placed on the top, and the mold is placed on the compaction density instrument. Different pressures (for example, 3T) can be set. The thickness of the lithium iron phosphate salt particles under different pressures can be read on the device. The powder compaction density of the lithium iron phosphate salt particles is ρ=m / v, where v=(S×H), m is the mass of the lithium iron phosphate salt particles, S is the bottom area of the mold, and H is the thickness of the lithium iron phosphate salt particles after compaction.
[0160] The powder resistivity of the lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, GB / T 33822-2017 can be referred to and a powder resistivity meter (Suzhou Jingge, ST2722 model) can be used for measurement. Specifically, a certain amount of lithium iron phosphate salt particles (for example, 1g) is weighed and added to the feeding chamber of the powder resistivity meter, and a pressure of 8MPa is applied. The forward resistivity and reverse resistivity of the lithium iron phosphate salt particles are tested respectively, and the average value of the two is taken as the powder resistivity of the lithium iron phosphate salt particles.
[0161] By making the lithium iron phosphate salt particles satisfy at least one of (a)-(e), the lithium iron phosphate salt particles can better achieve the technical effect of the present application.
[0162] The present application provides a method for preparing a positive electrode active material, the preparation method comprising: mixing lithium iron phosphate salt particles and lithium nickel cobalt manganese oxide particles,
[0163] The preparation process of lithium iron phosphate salt particles includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, optionally a carbon source, optionally a carbon film-forming agent, and optionally a modifier, and performing at least two sintering steps, wherein:
[0164] The temperature of the first sintering is 500℃-760℃, and can be 550℃-720℃;
[0165] The temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C.
[0166] In some embodiments, the temperature of the first sintering may be 500°C, 530°C, 550°C, 580°C, 600°C, 630°C, 650°C, 680°C, 700°C, 710°C,
[0167] The temperature of the second sintering may be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, or a value in the range consisting of any two of the above second sintering temperatures.
[0168] In some embodiments, the heating rates of the first sintering and the second sintering are independently 2° C. / min-20° C. / min.
[0169] In some embodiments, the heating rates in the first sintering and the second sintering are each independently 2°C / min, 5°C / min, 7°C / min, 10°C / min, 13°C / min, 15°C / min, 17°C / min or 20°C / min.
[0170] In some embodiments, the constant temperature sintering time of the first sintering is 1-6 hours. In some embodiments, the constant temperature sintering time of the first sintering can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0171] In some embodiments, the constant temperature sintering time of the second sintering is 2-12 hours. In some embodiments, the constant temperature sintering time of the second sintering can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours.
[0172] Compared to the traditional method of using high temperature to achieve particle growth, the lithium iron phosphate salt particles of the present application are sintered twice, and controlling the temperature of the two sinterings is conducive to preparing lithium iron phosphate salt particles having the primary average particle size and specific surface area of the present application. Furthermore, controlling the heating rate, sintering temperature and constant temperature sintering time of the first sintering and / or the second sintering helps to reduce side reactions, thereby better preparing the lithium iron phosphate salt particles of the present application. Furthermore, in the conventional high-temperature sintering process, the carbon coating layer on the surface of the particles is prone to cracking, reducing the integrity of the carbon coating. The present application performs large particle synthesis at low temperature, which is conducive to improving the consistency and uniformity of the surface carbon coating.
[0173] In some embodiments, the lithium iron phosphate salt particles are mainly obtained by the following preparation method: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sinterings, wherein:
[0174] The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%;
[0175] The carbon content of the material after the second sintering is 0.8 wt % to 2.0 wt %, and can be optionally 1.0 wt % to 1.6 wt %.
[0176] In some embodiments, the carbon content of the material after the first sintering can be 0.01 weight%, 0.05 weight%, 0.1 weight%, 0.15 weight%, 0.20 weight%, 0.25 weight%, 0.30 weight%, 0.35 weight%, 0.40 weight%, 0.45 weight%, 0.50 weight%, 0.55 weight%, 0.60 weight%, 0.65 weight%, 0.70 weight%, 0.75 weight%, 0.79 weight, or a value in the range consisting of any two of the above carbon contents; the carbon content of the material after the second sintering can be 0.8 weight%, 0.9 weight%, 1.0 weight%, 1.1 weight%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight%, 1.6 weight%, 1.7 weight%, 1.8 weight%, 1.9 weight%, 2.0 weight%, or a value in the range consisting of any two of the above carbon contents.
[0177] Adding a carbon source before the first sintering can effectively reduce the trivalent iron in the raw material and improve the purity and stability of the product. Furthermore, adding a lower carbon source content during the first sintering process is beneficial to reducing the barrier effect of the carbon layer on the growth of lithium iron phosphate particles, which is beneficial to the crystallization growth of the lithium iron phosphate salt particle precursor at a lower temperature. At the same time, the low carbon content during the first sintering process is also beneficial to the solid-phase diffusion reaction between the modifier that may be added and the lithium iron phosphate salt material, which is beneficial to achieve a higher concentration of metal ion doping. Increasing the added carbon content in the second sintering further improves the uniformity and integrity of the coating, which is beneficial to obtaining lithium iron phosphate salt particles with the carbon content of the embodiment of the present application.
[0178] In some embodiments, a raw material containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a modifier, and a carbon film-forming agent is provided, and sintering is performed at least twice.
[0179] In some embodiments, the mixing ratio of the lithium source, the iron source, and the phosphorus source satisfies, based on the atomic mole number of each element, Fe:P=(0.96-0.985):1, Li:Fe=(1.0-0.95):1.1.
[0180] In some embodiments, the mixing ratio of the iron source and the phosphorus source, calculated on the basis of the atomic moles of each element, satisfies Fe:P=0.96:1, Fe:P=0.965:1, Fe:P=0.97:1, Fe:P=0.975:1, Fe:P=0.98:1 or Fe:P=0.985:1.
[0181] In some embodiments, the mixing ratio of the lithium source and the iron source, calculated on the basis of the atomic moles of each element, satisfies Li:Fe=1.0:1.1, Li:Fe=0.99:1.1, Li:Fe=0.98:1.1, Li:Fe=0.97:1.1, Li:Fe=0.96:1.1 or Li:Fe=0.95:1.1.
[0182] In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent is (9-0.25): 1. In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent may be 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 0.8:1, 0.5:1 or 0.25:1.
[0183] In some embodiments, the lithium source is a lithium-containing compound. In some embodiments, the lithium source includes at least one of lithium dihydrogen phosphate, lithium oxalate, lithium carbonate, lithium oxide, lithium hydroxide, and lithium acetate. In some embodiments, the lithium source includes lithium carbonate.
[0184] In some embodiments, the iron source is an iron-containing compound. In some embodiments, the iron source includes at least one of ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, ferric oxide, and ferric oxyhydroxide. In some embodiments, the iron source includes ferric oxide.
[0185] In some embodiments, the phosphorus source is a phosphoric acid compound. In some embodiments, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate. In some embodiments, the phosphorus source includes phosphoric acid.
[0186] In some embodiments, the carbon source comprises at least one of citric acid, glucose, sucrose, starch, fructose, and lactose. In some embodiments, the carbon source comprises glucose.
[0187] In some embodiments, the carbon film-forming agent includes at least one of polyethylene glycol, polyaniline, polyacrylonitrile, polyvinyl pyrrolidone, and polyvinyl alcohol. In some embodiments, the carbon film-forming agent includes polyaniline.
[0188] In some embodiments, the modifier includes at least one of titanium dioxide, vanadium pentoxide, n-butyl titanate, ammonium metavanadate, niobium ethoxide, niobium oxalate, niobium pentoxide, magnesium hydroxide, and magnesium nitrate. In some embodiments, the modifier includes titanium dioxide.
[0189] By using the raw materials in the above ratio, it is beneficial to form the lithium iron phosphate salt particles of the present application.
[0190] In some embodiments, the lithium iron phosphate salt particles contain at least one of Ti, V, Mg, and / or Nb elements, and the content of the element is 1000ppm-10000ppm, optionally 2500ppm-6000ppm, calculated based on the total weight of the lithium iron phosphate salt particles.
[0191] In some embodiments, the content of the element may be selected to be 2500 ppm-6000 ppm. Specific options include 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, 3200ppm, 3300ppm, 3400ppm, 3500ppm, 3600ppm, 3700ppm, 3800ppm, 3900ppm, 4000ppm, 4100ppm, 4200ppm, 4300ppm, 4400ppm, 4500ppm, 4600ppm, 4700ppm, 4800ppm, 4900ppm, 5000ppm, 5100ppm, 5200ppm, 5300ppm, 5400ppm, 5500ppm, 5600ppm, 5700ppm, 5800ppm, 5900ppm or 6000ppm, or the range between any two of the above values.
[0192] By doping the lithium iron phosphate salt of the embodiment of the present application with one or more of the above elements and making the content thereof within the above range, it is possible to better achieve the metal bulk modification of the lithium iron phosphate salt particles while improving the primary average particle size of the lithium iron phosphate salt particles, further enhance the bulk ion transport capacity of the lithium iron phosphate salt particles, and improve the kinetic performance and gram capacity.
[0193] In some embodiments, a first pulverization is performed after a first sintering, and a second pulverization is performed after a second sintering, wherein:
[0194] The Dv50 of the product after the first pulverization is 300nm-1200nm, and can be optionally 400nm-1100nm;
[0195] The Dv50 of the product after the second pulverization is 500nm-5000nm, and can be optionally 700nm-2500nm.
[0196] In some embodiments, the Dv50 of the product after the first crushing can be 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, or a value in the range composed of the Dv50 of any two of the above products after the first crushing.
[0197] In some embodiments, the Dv50 of the product after the second crushing can be 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1700nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 2900nm, 3000nm, 3200nm, 3400nm, 3600nm, 3800nm, 4000nm, 4200nm, 4400nm, 4600nm, 4800nm, 5000nm, or a value in the range composed of the Dv50 of any two of the above products after the second crushing.
[0198] In some embodiments, comminution includes one or more of mechanical crushing, grinding, sand milling, and air flow crushing.
[0199] Controlling the Dv50 of the product after the first pulverization within the above range is conducive to reducing the growth barrier effect of the added carbon source and the possible doping elements on the lithium iron phosphate salt particle precursor crystal, and is helpful to prepare a micron-sized lithium iron phosphate salt particle precursor. By controlling the Dv50 value of the product after the second pulverization within the above range, it is helpful to obtain lithium iron phosphate salt particles having the primary average particle size of the present application.
[0200] [Positive electrode]
[0201] The present application provides a positive electrode plate, which includes the positive electrode active material as described in the present application or the positive electrode active material obtained by the preparation method as described in the present application.
[0202] In some embodiments, the compaction density of the positive electrode sheet is 3.0 g / cm 3 -3.5g / cm 3 .
[0203] In some embodiments, the compaction density of the positive electrode sheet can be 3.0 g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm3 、3.5g / cm 3 Or it can be a value in the range consisting of the compaction densities of any two of the above-mentioned positive electrode sheets.
[0204] The compaction density of the pole piece can be tested by methods and equipment known in the art. As an example, when the pole piece is coated on one side, the compaction density of the film layer on one side of the pole piece = m / (V1-V2); when the pole piece is coated on both sides, the compaction density of the film layer on one side of the pole piece = m / [2×(V1-V2)], where m represents the weight of the film layer, V1 represents the volume of the pole piece, and V2 represents the volume of the current collector. m can be obtained by subtracting the weight of the current collector from the weight of the pole piece. The product of the surface area of the pole piece and the thickness of the pole piece is the volume V1 of the pole piece. The product of the surface area of the pole piece and the thickness of the current collector is V2. The thickness of the current collector and the thickness of the pole piece are obtained by measuring the thickness of the empty foil in the lug area with a micrometer.
[0205] The compacted density of the positive electrode active material in the present embodiment is 3.0 g / cm 3 -3.5g / cm 3 , higher compaction density is beneficial to improving the energy density of secondary batteries.
[0206] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer includes a positive electrode active material, a binder and a conductive agent, and the positive electrode active material is the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application.
[0207] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0208] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0209] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0210] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0211] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0212] [Negative electrode]
[0213] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.
[0214] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0215] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0216] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0217] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0218] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0219] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0220] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0221] [Electrolytes]
[0222] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0223] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0224] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0225] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0226] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0227] [Isolation film]
[0228] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0229] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0230] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0231] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0232] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0233] [Secondary battery]
[0234] The present application provides a secondary battery, which includes the positive electrode sheet of the embodiment of the present application.
[0235] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 3 The secondary battery 5 is a square structure as an example.
[0236] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0237] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0238] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0239] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0240] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0241] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0242] [Electrical devices]
[0243] In addition, the present application also provides an electrical device, which includes the secondary battery of the embodiment of the present application.
[0244] In some embodiments, the power-consuming device of the embodiment of the present application may also include at least one of a battery module or a battery pack. The secondary battery, battery module, or battery pack may be used as a power source for the power-consuming device, or may be used as an energy storage unit for the power-consuming device. The power-consuming device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0245] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0246] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0247] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0248] Example
[0249] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0250] Example 1
[0251] 1. Preparation method
[0252] 1) Preparation of positive electrode active materials
[0253] Preparation of lithium iron phosphate particles:
[0254] Weigh lithium carbonate, ferric oxide, phosphoric acid, glucose, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added is such that the titanium content in the prepared lithium iron phosphate particles is 5000ppm) and polyaniline, wherein the weight ratio of Li element, Fe element and P element is such that Fe:P=0.968:1; Li:Fe=1:0.98, and the weight ratio of glucose to polyaniline is such that glucose:polyaniline=1:2. The amount of glucose and polyaniline added is such that after the first sintering, the carbon content accounts for 0.15% of the weight of the lithium iron phosphate precursor. Add water to the above substances to obtain a mixture slurry.
[0255] Use a ball mill to mix the mixture slurry evenly, grind it with a sand mill to obtain a slurry with a solid content of 38% and a Dv50 of 400nm, and spray dry it (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for the first sintering, and the heating rate is controlled at 5℃ / min, the insulation temperature is controlled at 650℃, and the insulation time is 4h. After the material is cooled, it is crushed by a mechanical mill to obtain a powder.
[0256] The obtained powder, glucose, polyaniline and water are mixed (based on the total weight of the lithium iron phosphate particles, the amount of glucose and polyaniline added is such that the carbon content of the product after the second sintering is 1.2%, and the weight ratio of glucose and polyaniline is such that glucose: polyaniline = 1:2), and the solid content is 40%. After uniform mixing, the slurry is obtained by ball milling and sand milling. The Dv50 of the insoluble matter in the slurry is 550nm. The slurry is spray dried (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for a second low-temperature sintering (the heating rate is controlled at 5℃ / min, the sintering temperature is 750℃, and the sintering time is 4h). After the material is cooled, it is crushed for the second time to an average particle size of 870nm. After demagnetization, lithium iron phosphate salt particles are obtained. The carbon content is 1.2%, and the Ti content in the lithium iron phosphate salt particles is 5000ppm. The obtained lithium iron phosphate salt particles are observed under a scanning electron microscope. The results are shown in the attached figure. Figure 2 shown.
[0257] Lithium nickel cobalt manganese oxide particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. The model is CPE-16, and the BET value and Dv50 value are shown in Table 1.
[0258] The lithium iron phosphate salt particles and the nickel cobalt manganese oxide lithium particles were mixed according to the mass listed in Table 1 to obtain the positive electrode active material.
[0259] 2) Preparation of positive electrode
[0260] 2.0 wt % of polyvinylidene fluoride binder was fully dissolved in N-methylpyrrolidone (NMP), and then 1.0 wt % of Super P, 0.5 wt % of carbon nanotubes and 96.5 wt % of the above positive electrode material were added and stirred and mixed to obtain a positive electrode slurry;
[0261] The positive electrode slurry was prepared at 252mg / 1540mm 2 The single-sided weight is evenly coated on the surface of the current collector aluminum foil, and then transferred to a vacuum drying oven for complete drying. The dried electrode sheet is rolled and punched to obtain the positive electrode sheet.
[0262] 3) Preparation of negative electrode sheet
[0263] Adding artificial graphite as a negative electrode active material, carbon black as a conductive agent, carboxymethyl cellulose as a thickener, and styrene-butadiene rubber as a binder into deionized water in a mass ratio of 0.9735:0.007:0.01:0.0095, and stirring evenly to obtain a negative electrode slurry;
[0264] Then the negative electrode slurry was mixed with 139mg / 1540mm 2 The single-sided weight is evenly coated on the copper foil, and the negative electrode sheet is obtained through drying, cold pressing and slitting.
[0265] 4) Preparation of isolation membrane
[0266] Polypropylene film is used as the isolation film.
[0267] 5) Preparation of batteries
[0268] The positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, the bare battery cell is welded with a pole ear, and the bare battery cell is placed in an aluminum shell and baked in a vacuum oven at 100°C for 8 hours, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static standing, hot and cold pressing, formation, shaping, capacity testing, etc. in sequence to obtain the lithium-ion battery of Example 1.
[0269] The preparation method of the battery of Example 2-5 is similar to that of Example 1, but the primary average particle size of the lithium iron phosphate salt particles is adjusted, as shown in Table 1. The preparation methods of Example 2-Example 5 differ from those of Example 1 in that:
[0270] Example 2: Lowering the Dv50 of the mixed slurry after the first grinding to 350 nm;
[0271] Example 3: Increasing the Dv50 of the mixed slurry after the first grinding to 1200 nm;
[0272] Example 4: Reducing the Dv50 of the mixed slurry after the first grinding to 450nm;
[0273] Example 5: Increasing the Dv50 of the mixed slurry after the first grinding to 1100 nm.
[0274] The preparation method of the battery of Example 6-7 is similar to that of Example 1, but the specific surface area value and carbon content of the lithium iron phosphate salt particles are adjusted, as shown in Table 1. The preparation method of Example 6-7 is different from that of Example 1 in that:
[0275] Example 6: The carbon content during the second sintering process is adjusted to 0.8%;
[0276] Example 7: The carbon content during the second sintering process was adjusted to 1.4%.
[0277] The preparation method of the battery of Example 8-9 is similar to that of Example 1, but the specific surface area value of the lithium iron phosphate salt particles is adjusted, as shown in Table 1. The preparation method of Example 8-9 is different from that of Example 1 in that:
[0278] Example 8: During the first sintering process, the weight ratio of glucose to polyaniline is 1:4;
[0279] Example 9: During the first sintering process, the weight ratio of glucose to polyaniline was 1:0.5.
[0280] The preparation method of the battery of Example 10-11 is similar to that of Example 1, but the specific surface area value of the nickel cobalt manganese oxide is adjusted, as shown in Table 1. The nickel cobalt manganese oxide particles of Example 10 were purchased from Guangdong Brunp Recycling Technology Co., Ltd., model CPE17; the nickel cobalt manganese oxide particles of Example 11 were purchased from Guangdong Brunp Recycling Technology Co., Ltd., model CPE18.
[0281] The preparation method of the batteries of Examples 12-14 is similar to that of Example 1, but the doping amount of the Q element is adjusted, as shown in Table 1. In the process of preparing the lithium iron phosphate salt particles, the difference from Example 1 is that;
[0282] Example 12: The temperature of the first sintering is controlled to be 590° C., the temperature of the second sintering is controlled to be 720° C., and the Ti content is 0 ppm;
[0283] Example 13: The temperature of the first sintering is controlled to be 620°C, the temperature of the second sintering is controlled to be 740°C, and the Ti content is controlled to be 2500ppm;
[0284] Example 14: The temperature of the first sintering was controlled to be 655°C, the temperature of the second sintering was controlled to be 755°C, and the Ti content was controlled to be 6000ppm.
[0285] The preparation method of the battery of Examples 15-18 is similar to that of Example 1, but the Dv50 value of the lithium iron phosphate particles or the lithium nickel cobalt manganese oxide particles is adjusted, as shown in Table 1. The preparation method of Examples 15-18 is different from that of Example 1 in that:
[0286] Example 15: Controlling the Dv50 of the crushed product after the second sintering to be 870m;
[0287] Example 16: Controlling the Dv50 of the powder after the second sintering to be 3500nm;
[0288] The nickel-cobalt-manganese-oxide lithium particles of Example 17 were purchased from Guangdong Brunp Recycling Technology Co., Ltd., model number CPE19;
[0289] The lithium nickel cobalt manganese oxide particles of Example 18 were purchased from Guangdong Brunp Recycling Technology Co., Ltd., model number CPE20.
[0290] The preparation method of the battery of Examples 19-20 is similar to that of Example 1, but the mass blending ratio of the lithium iron phosphate salt particles and the lithium nickel cobalt manganese oxide particles is adjusted, as shown in Table 1.
[0291] The preparation method of the battery of Comparative Example 1 is similar to that of Example 1, but the lithium iron phosphate salt particles used are different from those of Example 1. The lithium iron phosphate salt particles used in Comparative Example 1 are purchased from Hunan Yuneng New Energy Battery Materials Co., Ltd., model CPF-087-1, and specific parameters are shown in Table 1.
[0292] The preparation method of the battery of Comparative Example 2 is similar to that of Example 1, but the lithium iron phosphate salt particles used are different from those of Example 1. The lithium iron phosphate salt particles used in Comparative Example 2 are purchased from Hunan Yuneng New Energy Battery Materials Co., Ltd., model CPF-087-2, and specific parameters are shown in Table 1.
[0293] The preparation method of the battery of Comparative Example 3 is similar to that of Example 1, but the primary average particle size and specific surface area of the lithium iron phosphate salt particles are adjusted, as shown in Table 1. The preparation method of Comparative Example 2 is different from that of Example 1 in that Comparative Example 2 only uses one sintering process, the sintering temperature is 750°C, and the carbon content of the sintered product is 1.2%.
[0294] The preparation method of the battery of Comparative Example 4 is similar to that of Example 1, but the primary average particle size, specific surface area and carbon content of the lithium iron phosphate salt particles are adjusted, as shown in Table 1. The preparation method of Comparative Example 3 is different from that of Example 1 in that the carbon content of the second sintering is reduced to 0.7% in Comparative Example 3, thereby adjusting the BET and primary average particle size.
[0295] 2. Battery performance test
[0296] 1. Performance test of positive electrode active materials
[0297] 1) Primary average particle size test method of lithium iron phosphate particles
[0298] The electrode sheet is cut open perpendicularly to the large surface of the positive electrode sheet using an argon ion beam to expose the cross section, which is photographed using a scanning electron microscope. The particle size of the lithium iron phosphate salt particles is statistically analyzed using the long diameter statistical method. Specifically, the total number of lithium iron phosphate salt particles with a primary particle size greater than 80nm and the primary particle size and the sum of the lithium iron phosphate salt particles with a primary particle size greater than 80nm can be counted in the electron microscope scanning photo. The primary average particle size of the lithium iron phosphate salt particles = the primary particle size of the total lithium iron phosphate salt particles / the total number of lithium iron phosphate salt particles. In the primary particle size statistical process, particles with a primary particle size of 0 < ≤ 80nm are not within the statistical range.
[0299] 2) Dv50 value test method
[0300] Lithium iron phosphate particles: GB / T19077.1-2016 can be referred to, and the Dv50 value of the lithium iron phosphate particles can be determined using a laser particle size analyzer (MalvernMaster Size 3000).
[0301] Nickel cobalt manganese oxide lithium particles: GB / T19077.1-2016 can be referred to, and the Dv50 value of the nickel cobalt manganese oxide lithium particles can be determined using a laser particle size analyzer (MalvernMaster Size 3000).
[0302] 3) Specific surface area (BET) test method
[0303] According to the GB / T19587-2017 test standard method, the gas adsorption method is used to test the specific surface area of lithium iron phosphate particles and nickel cobalt manganese oxide particles, as follows: lithium iron phosphate particles or nickel cobalt manganese oxide particles are taken as samples, the sample tube is immersed in -196°C liquid nitrogen, and the adsorption amount of nitrogen on the solid surface at different pressures is measured at a relative pressure of 0.05-0.30. The single-layer adsorption amount of the sample is obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the sample.
[0304] 4) Test method for carbon content of lithium iron phosphate particles
[0305] The carbon content of lithium iron phosphate particles was tested by infrared absorption method after burning them in a high-frequency induction furnace. The specific testing process was based on the standard GB / T 20123-2006 / ISO 15350:2000.
[0306] 5) Test method for the doping amount of Q element (such as Ti element) in lithium iron phosphate particles
[0307] The test method for the Q element content of lithium iron phosphate particles is carried out in accordance with GB / T 33822-2017.
[0308] 6) Test method for solid content of positive electrode slurry
[0309] Electronic balance (accuracy 0.0001), oven, glass drying tray. Take 8-10g of positive electrode slurry sample and spread it evenly on the sample tray, and record the mass of positive electrode slurry before drying as A. Put the sample tray with positive electrode slurry sample into the oven and heat it at 130℃ for 5h. Take it out after drying and cooling, and record the mass of positive electrode slurry after drying. Dry it several times, and record the mass of positive electrode slurry sample after drying to constant weight as B. Positive electrode slurry solid content = (A / B) × 100%.
[0310] 7) Cathode slurry filtration performance test method
[0311] Fold a 200-mesh filter into an inverted triangle, place it in a 500-ml beaker, and pour in 500 ml of the prepared positive electrode slurry (pour all of it). Start timing when the slurry begins to flow out from the tip of the filter, and record the filtration time when the slurry in the beaker reaches 300 ml.
[0312] 8) Measurement of η value of lithium iron phosphate particles
[0313] First, a button cell is prepared using lithium iron phosphate particles as the positive electrode active material. The specific button cell preparation process is as follows: 2.0000g of lithium iron phosphate particles are mixed with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then added to 2.5g of organic solvent N-methylpyrrolidone, and mixed thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum heat preservation at 120°C for 12h to obtain a positive electrode sheet. Weigh the weight of the positive electrode sheet, where the loading amount of lithium iron phosphate particles is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.
[0314] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V was extracted and recorded as C1, and the capacity value at a discharge voltage of 2.0V was extracted and recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50uA.
[0315] 2. Battery performance test
[0316] 1) The battery capacity in grams
[0317] Place the battery in a 25℃ oven environment and let it stand for 2h until the battery temperature remains at 25℃; discharge the battery at a 1 / 3C constant current to 2.0V; pause for 5min; charge the battery at a 1 / 3C constant current to 4.35V, then charge at a 4.35V constant voltage to a cutoff current of 0.05C; pause for 5min.
[0318] Discharge the battery at a constant current of 1 / 3C to 2.0V. This step is the actual battery cell test capacity. Combined with the mass of the positive electrode active material, the gram capacity of the battery can be calculated. Gram capacity = capacity / mass of the positive electrode active material.
[0319] 2) Test method for compaction density of positive electrode
[0320] When the pole piece is coated on one side, the compaction density of the film layer on one side of the pole piece = m / (V1-V2); when the pole piece is coated on both sides, the compaction density of the film layer on one side of the pole piece = m / [2×(V1-V2)], where m represents the weight of the film layer, V1 represents the volume of the pole piece, and V2 represents the volume of the current collector. m can be obtained by subtracting the weight of the current collector from the weight of the pole piece. The product of the surface area of the pole piece and the thickness of the pole piece is the volume V1 of the pole piece, and the product of the surface area of the pole piece and the thickness of the current collector is V2. The thickness of the current collector and the thickness of the pole piece are obtained by measuring the thickness of the empty foil in the tab area with a micrometer.
[0321] III. Analysis of test results of various embodiments and comparative examples
[0322] The batteries of the embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The parameters of the positive electrode active materials are shown in Table 1, and the performance test results are shown in Table 2.
[0323]
[0324] Table 2 Performance test results
[0325]
[0326] According to the results in the above table, it can be seen from Examples 1-20 and Comparative Example 1 that increasing the primary average particle size of the lithium iron phosphate salt particles and reducing their specific surface area can increase the solid content and filtration performance of the positive electrode slurry, which is beneficial to improving processing problems. It can be seen from Examples 1-20 and Comparative Example 2 that reducing the specific surface area of the lithium iron phosphate salt particles is beneficial to increasing the solid content and filtration performance of the positive electrode slurry, which is beneficial to improving processing problems. It can be seen from Examples 1-18 and Comparative Example 3 that the primary average particle size of the lithium iron phosphate salt particles of the present application is beneficial to maintaining a good gram capacity. It can be seen from Examples 1-18 and Comparative Example 4 that when the BET of the lithium iron phosphate salt particles is too small, the gram capacity of the secondary battery will be reduced. In summary, when the primary average particle size of the lithium iron phosphate salt particles is 500-3000nm and the specific surface area BET is 3m 2 / g-8m 2 / g, and the specific surface area of lithium nickel cobalt manganese oxide particles is 0.4m 2 / g-2.0m 2 / g, which can improve the processing performance of the positive electrode slurry while taking into account the gram capacity of the secondary battery.
[0327] By the attached Figure 1 From Figures 1a and 1b, it can be seen that the nickel cobalt manganese oxide particles and the lithium iron phosphate salt particles are evenly mixed, and the lithium iron phosphate salt particles densely fill the pores of the nickel cobalt manganese oxide particles. Figure 2 The scanning electron microscope image shows the microscopic morphology of the lithium iron phosphate salt particles in Example 1 of the present application. It can be seen from the image that the lithium iron phosphate salt in Example 1 of the present application presents the morphology of large single crystals.
[0328] It can be seen from Examples 1-5 that when the primary average particle size of the lithium iron phosphate particles is controlled to be 500-3000 nm, the processing performance of the positive electrode slurry can be improved while taking into account the gram capacity of the secondary battery.
[0329] It can be seen from Examples 1, 6-7 and 10-11 that the BET value of the lithium iron phosphate particles is controlled to be 3m 2 / g-8m 2 / g, and control the BET value of the nickel cobalt manganese oxide particles to 0.4m 2 / g-2.0m 2 / g, the gram capacity of the secondary battery can be taken into account while improving the processing performance of the positive electrode slurry.
[0330] It can be seen from Example 1 and Examples 8-9 that increasing the proportion of the carbon source film-forming agent is beneficial to achieving dense coating of the carbon layer. The dense degree of carbon coating in the present application is beneficial to further improving the kinetic performance and gram capacity of the secondary battery.
[0331] It can be seen from Example 1 and Examples 12-14 that adding metal elements, such as titanium, to lithium iron phosphate salt particles can improve the kinetic properties of the positive electrode active material. Further, increasing the content of the metal element, for example, within the range of 1000-10000 ppm, is conducive to further improving the kinetic properties and minimizing the impact on the gram capacity of the lithium iron phosphate salt particles.
[0332] It can be seen from Example 1 and Examples 15-18 that when the Dv50 of the lithium iron phosphate salt particles is 500-5000nm, the Dv50 of the nickel cobalt manganese oxide particles is 1200-20000nm, and the ratio of the two satisfies 1:(1-50), it is beneficial to improve the compaction density of the positive electrode sheet.
[0333] It can be seen from Example 1 and Examples 19-20 that controlling the mass percentage of lithium iron phosphate salt particles and lithium nickel cobalt manganese oxide particles within an appropriate range, for example, when the mass percentage of lithium iron phosphate salt particles is 5%-80% and the mass percentage of lithium nickel cobalt manganese oxide particles is 95%-20%, helps to further balance the processing performance, electrical properties and cost of the positive electrode active material.
[0334] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises lithium iron phosphate particles and lithium nickel cobalt manganese oxide particles, wherein the primary average particle size of the lithium iron phosphate particles is 500-3000 nm, and the specific surface area of the lithium iron phosphate particles is 3 m 2 / g-8m 2 / g, the specific surface area of the lithium nickel cobalt manganese oxide particles is 0.4m 2 / g-2.0m 2 / g.
2. The positive electrode active material according to claim 1, wherein the lithium iron phosphate salt particles have the molecular formula Li m1 Fe x1 P y1 O z1 Q q1 , where Q comprises at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95 ≤ m1 ≤ 1.15, 0.9 ≤ x1 ≤ 1, 0.95 ≤ y1 ≤ 1, 3.5 ≤ z1 ≤ 4, 0 < q1 ≤ 0.1, and / or The lithium nickel cobalt manganese oxide particles have a molecular formula of LiR x2 Ni y2 Co z2 Mn 1-x2-y2-z2 O2, where The R includes at least one of Cr, Ti, V, Mg, Al, and Nb, 0≤x2<1, 0<y2<1, 0<z2<1, 0<x2+y2+z2<1.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The primary average particle size of the lithium iron phosphate salt particles is 650-2500 nm.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The BET of the lithium iron phosphate particles is 4m 2 / g-7m 2 / g, the BET of the nickel cobalt manganese oxide particles is 0.6m 2 / g-2.0m 2 / g.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that Calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is 0.8 wt %-2.0 wt %.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that Calculated based on the total weight of the lithium iron phosphate salt particles, the carbon content of the lithium iron phosphate salt particles is 1.0 wt %-1.6 wt %.
7. The positive electrode active material according to any one of claims 2 to 6, characterized in that The Q comprises at least one of Ti, V, Mg and Nb; Calculated based on the total weight of the lithium iron phosphate salt particles, the content of Q in the lithium iron phosphate salt particles is 1000-10000 ppm.
8. The positive electrode active material according to any one of claims 1 to 7, characterized in that The Dv50 of the lithium iron phosphate salt particles is 500-5000nm.
9. The positive electrode active material according to any one of claims 1 to 8, characterized in that The Dv50 of the nickel cobalt lithium manganese oxide particles is 1200-20000nm.
10. The positive electrode active material according to any one of claims 1 to 9, characterized in that The Dv50 of the lithium iron phosphate salt particles is 870-1500nm, and the Dv50 of the lithium nickel cobalt manganese oxide particles is 1800-4200nm.
11. The positive electrode active material according to any one of claims 1 to 10, characterized in that Based on the total mass of the positive electrode active material, the mass percentage of the lithium iron phosphate salt particles is 5%-80%.
12. The positive electrode active material according to any one of claims 1 to 11, characterized in that Based on the total mass of the positive electrode active material, the mass percentage of the lithium nickel cobalt manganese oxide particles is 20%-95%.
13. The positive electrode active material according to any one of claims 1 to 12, characterized in that The capacity proportion of the lithium iron phosphate salt particles is η≥88%, and η is defined as: The battery having the lithium iron phosphate particles as the positive electrode active material is charged and discharged twice at a constant current of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted at a discharge voltage of 2.0V is recorded as C2, and η=C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50uA.
14. The positive electrode active material according to any one of claims 1 to 13, characterized in that The lithium iron phosphate salt particles satisfy at least one of (a) to (e): a) the Dv10 of the lithium iron phosphate particles is ≥200nm; b) the Dv90 of the lithium iron phosphate particles is ≤10000m; c) the Dv99 of the lithium iron phosphate particles is ≤12000nm; d) The powder compaction density of the lithium iron phosphate salt under a pressure of 3T is ≥2.25g / cm 3 ; e) The powder resistivity of the lithium iron phosphate salt is less than 60Ω·cm.
15. A method for preparing a positive electrode active material, characterized in that: The preparation method comprises: mixing lithium iron phosphate salt particles and lithium nickel cobalt manganese oxide particles, The preparation process of the lithium iron phosphate salt particles includes: providing raw materials containing at least a lithium source, an iron source, and a phosphorus source, and performing at least two sintering steps, wherein: The temperature of the first sintering is 500℃-760℃; The temperature of the second sintering is 700℃-800℃.
16. The preparation method according to claim 15, characterized in that: The lithium iron phosphate salt particles are mainly obtained by the following preparation method: Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein: The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%; The carbon content of the material after the second sintering is 0.8 wt%-2.0 wt%.
17. The preparation method according to claim 15 or 16, characterized in that: The lithium iron phosphate salt particles contain at least one of Ti, V, Mg, and / or Nb elements, and the content of the element is 1000ppm-10000ppm based on the total weight of the lithium iron phosphate salt particles.
18. The preparation method according to any one of claims 15 to 17, characterized in that: The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein: The Dv50 of the product after the first crushing is 300nm-1200nm; The Dv50 of the product after the second pulverization is 500nm-5000nm.
19. A positive electrode plate, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 14 or the positive electrode active material obtained by the preparation method according to any one of claims 15 to 18.
20. The positive electrode sheet according to claim 19, characterized in that: The compaction density of the positive electrode sheet is 3.0 g / cm 3 -3.5g / cm 3 .
21. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet as claimed in claim 19 or 20.
22. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 21.
Citation Information
Patent Citations
Lithium iron phosphate / carbon composite material and preparation method and application thereof
CN110137476A
Positive electrode material, positive plate and secondary battery
CN115172698A
Mixed positive electrode material, positive electrode plate, preparation method, battery and device
CN115280551A
Secondary battery
CN115528296A
Composite electrode and preparation method thereof, battery and electric equipment
CN115810719A
Cited By
Positive electrode material, positive electrode plate, battery and electric device
CN121054653A